Post-Cesarean Peritonitis Caused by Hysterorrhaphy Dehiscence with Puerperal Acute Abdomen Syndrome - Pavoković, Dino; Cerovac, Anis; Ljuca, Dženita; Habek, Dubravko (Zeitschrift für Geburtshilfe und Neonatologie, 2020)
We present an overview of the case of a patient with early hysterorrhaphy dehiscence (uteroperitoneal fistula) with endomyometritis and post-cesarean section peritonitis and puerperal acute abdomen in a 35-year-old puerpera. A exploratory relaparotomy, necrectomy, and resuture of the dehiscent part of the hysterotomy were performed with placement of hemostatic sponges on the same portion of the uterus with good recovery.
Keywords: caesarean section; acute abdomen; hysterorrhaphy; dehiscence